Chronic lung disease in full‐term infants: Characteristics and neonatal intensive care outcomes in infants referred to children's hospitals. Issue 9 (25th May 2022) - Mikhael, Michel; Cleary, John P.; Zaniletti, Isabella; Truog, William E.; Ibrahim, John; DiGeronimo, Robert; Cuna, Alain; Kielt, Matthew J.; Coghill, Carl H.; Vyas‐Read, Shilpa; Yallapragada, Sushmita; Engle, William A.; et al.
Abstract: Objective: To describe characteristics, outcomes, and risk factors for death or tracheostomy with home mechanical ventilation in full‐term infants with chronic lung disease (CLD) admitted to regional neonatal intensive care units. Study Design: This was a multicenter, retrospective cohort study of infants born ≥37 weeks of gestation in the Children's Hospitals Neonatal Consortium. Results: Out of 67, 367 full‐term infants admitted in 2010–2016, 4886 (7%) had CLD based on receiving respiratory support at either 28 days of life or discharge. 3286 (67%) were still hospitalized at 28 days receiving respiratory support, with higher mortality risk than those without CLD (10% vs. 2%, p  < 0.001). A higher proportion received tracheostomy (13% vs. 0.3% vs. 0.4%, p  < 0.001) and gastrostomy (30% vs. 1.7% vs. 3.7%, p  < 0.001) compared to infants with CLD discharged home before 28 days and infants without CLD, respectively. The diagnoses and surgical procedures differed significantly between the two CLD subgroups. Small for gestational age, congenital pulmonary, airway, and cardiac anomalies and bloodstream infections were more common among infants with CLD who died or required tracheostomy with home ventilation ( p  < 0.001). Invasive ventilation at 28 days was independently associated with death or tracheostomy and home mechanical ventilation (odds ratio 7.6, 95% confidence interval 5.9–9.6, p  < 0.0001). Conclusion: Full‐term infants with CLD are at increased risk for morbidity and mortality. We propose a severity‐based classification for CLD in full‐term infants. Future work to validate this classification and its association with early childhood outcomes is necessary.